Genotypes and spatial configurations of public art museums in Japan - Yunfei Xie; Muhan Shen; Nobuaki Furuya (Journal of Asian Architecture and Building Engineering)
The social role of museums has continued to shift according to evolving social, economic, and cultural contexts. The transition from a single exhibition educational role to a more diversified role presents challenges in terms of the spatial configuration of museums, thereby highlighting areas for broadening the current understanding of spatial layouts. This report quantitatively analyzes the spatial configurations of 120 public art museums in Japan based on space syntax theory to delineate the characteristics, trends, and genotypes of the various configurations. First, we assess spatial configuration parameters to identify key characteristics and trends. Then, we apply syntactic and statistical analyses to identify and classify spatial genotypes. The results indicate that spatial configurations exhibit decreasing trends in the spatial concepts of stasis and axis and increasing trends in the spatial concepts of route and network. The concept of movement increases in terms of short-distance movement and exhibits high traversability. Four genotypes are identified, each with distinct integration cores and movement patterns. The insights provided herein highlight the adaptability of museum spatial configurations to diverse societal demands and offer robust guidance for future museum design.